Hanseníase: os modelos sociais da doença - Costa, Elizabeth Parente (2015)
The research proposes a study of the social representations of leprosy, we seek three times to understand the sense of every society and their dynamics in relation to disease. The first in the city of Sobral/CE, where we carry out research in the years 2008 and 2009; the second moment in the city of Mogi das Cruzes/SP, with a man who has gone through several periods of hospitalization and overcame the stigma through work aimed at manufacture of prosthetic patients amputees; and the third time in New Delhi in India, where we find the largest number of leprosy patients. The places chosen for the field work were selected after repeated bibliographical research, readings of scholarly articles, medical texts and physicians about the disease and mainly with the data of the World Health Organization (WHO) and of the Brazilian Institute of Geography and Statistics (IBGE). We investigate the sociocultural reality of people afflicted by illness and how these could be with the disease